Analog of the mean-value theorem for polynomials of special form - Trofymenko, O. D. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
A mean value theorem for polynomials of a special form is proved. The case of a sum over vertices of a regular polygon is studied and a criterion for the equation of a special form to be satisfied is obtained.